Crime and Local Inequality in South Africa - Demombynes, Gabriel (World Bank, Washington, DC, 2014)
The authors examine the effects of local inequality on property and violent crime in South Africa. Their findings are consistent with economic theories relating inequality to property crime, and also with sociological theories that imply that inequality leads to crime in general. Burglary rates are 20-30 percent higher in police station jurisdictions that are the wealthiest among their neighbors, suggesting that criminals travel to neighborhoods where the expected returns from burglary are highest. The authors do not find evidence that inequality between racial groups fosters interpersonal conflict at the local level.